Inspeksi Teknis dan Pengoperasian Sistem Pendingin Semi Contact Freezer untuk Cold Storage di Lampulo Banda Aceh - Suhaeri, Suhaeri; Bakhtiar, Dandi; Away, Yuwaldi; Lubis, Rakhmad Syaputra; Muslimsyah; Safwan (Yayasan Kawanad, 2025)
This community service activity was conducted to perform a technical inspection and evaluate the operation of the semi-contact freezer cooling system in Lampulo, Banda Aceh, established to support the development of the local fisheries sector. The system utilizes Air Blast Freezer (ABF) technology, operating at temperatures ranging from 0°C to -40°C for fish preservation through cooling and freezing methods. The facility, valued at IDR 465,312,000, was constructed by the Banda Aceh City Food, Agriculture, Maritime Affairs, and Fisheries Service in collaboration with CV. Juang Karya during the period of July to October 2022. Commissioning tests were conducted to verify compliance with the technical specifications outlined in the work contract. Inspection results confirmed that the system operated in accordance with specifications, with products packaged using LDPE plastic and cardboard. The operation of this system is expected to reduce losses due to fish spoilage and enhance food security for the Banda Aceh community.